Clínica Comunitaria Esperanza Pediátrica: The Development and Early Outcomes of a Bilingual Medical Home for Uninsured Hispanic Children - Im, Alex; Tosi, Amanda; Taylor-Fishwick, Jonathan; Sheehan, Brynn; Sriraman, Natasha; Leader, Alexandra (Journal of Student-Run Clinics, 2022)
The uninsured Hispanic pediatric population in the United States faces significant challenges in accessing medical care due to language barriers, citizenship status, and limited access to health insurance. Clínica Comunitaria Esperanza Pediátrica (CCE-P) is a bilingual student-run free clinic created to provide healthcare to the underserved population in southeastern Virginia. This study further details the creation, implementation, and early outcomes of CCE-P as well as barriers encountered throughout the process. It describes four critical steps in establishing CCE-P, including leveraging existing institutional partnerships, ensuring high standards of care, prioritizing community outreach, and implementing a quality improvement program. Study outcomes include a demographic characterization of the 46 pediatric patients served by CCE-P, a description of clinic services, and an analysis of gaps in care and strategies to provide more comprehensive health services. This publication serves as an outline to an adaptable model that other organizations may use to establish similar clinics in their own communities.